2005
DOI: 10.1002/anie.200500782
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of the Reaction Mechanism for the Palladium‐Catalyzed Synthesis of Vinyl Acetate

Abstract: Finding the right pathway: Reaction of isotopomers of ethylene with acetate species (see scheme) adsorbed on a Pd(111) surface in ultrahigh vacuum has shown that vinyl acetate is produced by insertion of ethylene into the acetate species to form an acetoxyethyl intermediate, which decomposes by β‐hydride elimination to yield vinyl acetate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
82
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(87 citation statements)
references
References 16 publications
3
82
2
Order By: Relevance
“…The calculated barriers indicate that there is a change in the reaction mechanism from that found over Pd(111) [19,36]. Despite the high gold coverage, molecular oxygen can still dissociate on these surfaces as the result of the noncontiguous Pd pairs, which provide Pd atoms within the two bridge sites across the four-fold hollow site.…”
Section: (D) Denisty Functional Theory On Au/pd Alloy Surfacesmentioning
confidence: 93%
See 2 more Smart Citations
“…The calculated barriers indicate that there is a change in the reaction mechanism from that found over Pd(111) [19,36]. Despite the high gold coverage, molecular oxygen can still dissociate on these surfaces as the result of the noncontiguous Pd pairs, which provide Pd atoms within the two bridge sites across the four-fold hollow site.…”
Section: (D) Denisty Functional Theory On Au/pd Alloy Surfacesmentioning
confidence: 93%
“…6, there is a relatively rapid reduction in the intensity of the acetate infrared feature (at ~1414 cm -1 ) when pressurized by ~1×10 -4 Torr of ethylene at 327 K. The decrease in the acetate signal intensity confirms that acetate species react with ethylene and the plot (•) shows the variation in intensity of the 1414-cm -1 acetate feature as a function of time. Another peak appears at ~1320 cm -1 as the acetate species have been removed assigned to ethylidyne formation on Pd(111) [19]. Calibration experiments show that the intensity of the 1414-cm -1 feature is proportional to the acetate coverage so that this plot represents a change in coverage of the acetate species as a function of time.…”
Section: (B) Surface and Catalytic Chemistry Of Clean Pd(111) Surfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is found that the reaction proceeds on Pd(111) via the insertion of adsorbed ethylene into the O-Pd bond of the surface acetate species [6] to form an acetoxyethyl-palladium intermediate, which decomposes via a b-hydride elimination reaction to yield VAM [7,8]. This reaction route, first proposed by Samanos [9] was confirmed using density functional theory (DFT) calculations which were able to rather precisely calculate the energies of the elementary steps in the reaction [8].…”
Section: Introductionmentioning
confidence: 99%
“…This implies that, if adsorbed acetate and ethylene do react on Pd(100), this will ultimately result in VAM being formed on a relatively uncrowded surface. The surface chemistry of VAM has been explored on clean and oxygen-covered Pd(100) surfaces [13] and indeed it is found that it thermally decomposes on the surface at *300 K implying that it will decompose on Pd(100) surfaces under the conditions (temperatures greater than 300 K) that the titration experiments and catalytic reactions [6][7][8] are carried out.…”
Section: Introductionmentioning
confidence: 99%